Enhancing Student Comprehension of Glucose Metabolism Visualization Through Virtual Simulation Platform: An Educational Approach - Luna Ge; Tingting Feng; Shuo Cao; Hang Yin; Yuang Zhang; Jihong Pan; Wei Chen; Kai Cheng; Lin Wang (Pharmacology Research & Perspectives)
ABSTRACT With the rapid progression of biotechnology, the significance translational research on glycolysis in molecular pharmacology has become increasingly evident. To deepen students' understanding of glycolytic processes and facilitate their comprehension of drug action mechanisms, we have developed a visual virtual simulation platform dedicated glycolysis. The educational approach commenced with theoretical lectures on glycolysis, followed by practical laboratory sessions where students measured glycolysis‐related parameters such as hexokinase, pyruvate kinase, and lactate. Students then engaged with the virtual simulation training platform to explore glycolytic stress tests and positron emission tomography/computed tomography (PET/CT) imaging, with their progress tracked through an assessment mode. The study involved 67 s‐year undergraduate students majoring in biomedical sciences, all of whom had received instruction in glucose metabolism theories and completed the associated questionnaires. The results showed that the students gained a deeper understanding of glycolysis and the clinical application of PET/CT imaging in the context of glycolysis. The majority also agreed that the integration of scientific and clinical cases in teaching is beneficial and that the project sparked their interest in scientific research. These findings align with existing literature that emphasizes the importance of innovative educational tools in enhancing student engagement and understanding of the underlying theories of the curriculum. This project designed an innovative glycolytic metabolism teaching system encompassing the monitoring of traditional glycolytic indicators, glycolytic stress tests, and PET/CT imaging based on glycolysis. The visual virtual simulation platform for glycolysis can serve as an innovative educational tool in the molecular pharmacology curriculum or other courses involving glycolysis, assisting students in deeply understanding the molecular mechanisms of glycolysis and its significance in disease and drug action.